Labour-market reforms in Europe: repairing problems or investing to prevent? - Andersen, Torben; Keuschnigg, Christian (Gütersloh, 2018)
"For most people, obtaining economic and social opportunities depends on access to labour-markets. Effective and flexible labour-markets allow economies to cope more easily with ageing and the disruptions of innovation and globalisation. Positive outcomes include the ability for women and men to reconcile work and family life adequately; young people’s ability to make a smooth transition from education to work; and robust labour-market integration for immigrants, allowing them to become active contributors to the economy and the welfare state. Policymakers must strike a balance between preventive and corrective strategies. If a country fails to implement preventive measures, it must later make policy corrections on an ex post basis, which often entail very high costs. A survey of 1,058 experts evaluates both the need for reform and actual reform performance, as measured by the frequency and quality of reform, within the EU-28 countries. The survey covers five areas of social inclusion, including poverty prevention, education, labour-market access, social cohesion and non-discrimination, and health. While there is significant variation across member states, experts perceive the most urgent need for reform in the area of improving access to labour-markets; however, reform performance here is middling at best."